Politics of labour unionism in the Implementation of national minimum wage in Osun State Civil Service, Nigeria - Bamidel, AbdulRasheed Hamza; Ambali, AbdulRauf; O. Ibrahim, Salawu (Faculty of Administrative Science and Policy Studies, 2024)
Labour unionism has been seen over the years as one of the most widely recognized and well-known in every organization‘s workforce, which seeks to protect the rights and interests of employees from erratic economic exploitation. The study work, therefore, explored the main thrusts of labour unionism in the implementation of the national minimum wage in Osun State Civil Service, Nigeria. To realize the central objective, the study used mixed methods (quantitative and qualitative) and data were generated both from primary and secondary sources. The population of civil servants in the Ministries, Departments, and Agencies (MDAs) in Osun state was 50254 and the sample size for the study was 400 using Taro Yamane formulae, and a simple percentage was utilised for the quantitative data analysis. Findings from the study revealed that labour unions pressurise for a decent wage and the implementation of a national minimum wage. Also, labour unions and state governments scientifically brainstorm on workers' requests. The Paper concluded that Labour unions in Osun are monitoring the activities of the government and its policies on behalf of the workers to ensure that government does not act illegally or unethically. The paper recommended that government should try as much as possible to maintain a good and cordial relationship with their employers/union members to avoid clashes that may wrench the organisation thus affecting organizational performance.